A TREATISE ON 43/77TH VERSE OF QURAN (ZUHKRUF CHAPTER) -FROM THE NOTES BY SEYYİD FEYZULLAH FİNDİKİ- - Şaban KARASAKAL (Fırat University, 2019)
Sirnak and its surroundings, before and after Islam, remained under the rule of various principality and states. With the spread of Islam in the region, the scientific movements increased there. Too many scholar grew up in Sirnak region as this movements continued increasingly from the first periods. Most of these scholars were the peak people in the education of Arabic-taught schools. Most of them wrote books and treatises in various fileds as well they taught. Most of these books written by them are related with the efforts of understanding of Quran. This situation continues in the region in part, and some scholar grow up. One of the major figures from this region is Findiki Sayyid Fayzullah Erzen (Sayyid Feyzullah Erzen b. Sheikh Muhammed b Sheikh Hassan Al-Buhti Al-Findiki), who has works in various fields. We have not some of his works today. As for the present works of him; some of them are published and some of them are hand-written and remain to be be interested in. When we look at his work named Levâmi’ul-Cevâhir bi İsnâ Aşere Fennen Yücâhir we see that it contains some assessments concerning scholastic disciplines like commentary of Quran, hadith, kelam as well as the different fields like geography, nahiv (Arabic grammar), qıraat (reading of Quran), sarf (Arabic morphology) and literature. In this paper, we will try to translate the assessments on the 77th verse of Zukhruf (44th chapter of Quran) from his book called Levami'u'l-Cevahir bi İthna Ashara Fennen Yucahir. Seyyid Feyzullah, in this treatise, deals with the expression of “yâ mâliku”, which takes place in this verse. He searchs which meaning could be understood from this expression in case it read with “tarkhım”